O IMAGINÁRIO DE AN NEUF DE AIMÉ CÉSAIRE À LUZ DA MITOCRÍTICA DE GILBERT DURAND (Polifonia, 1994)
ABSTRACT: This paper dives into Aimé Césaire's poem "An Neuf", using Gilbert Durand's framework, with the aim of disenangling the imagistic web that weaves various dimensions of the text, such as: semantic, mythic, historical and metapoetic.